Advocacy and Public Policy Perceptions and Involvement of College Health Promotion Students. Issue 5 (September 2019) - Conrad, Eric J.; Becker, Mikaela; Brandley, Elizabeth; Saksvig, Emilie; Nickelson, Jen
Understanding the advocacy and public policy training needs of our future health promotion workforce is crucial if we are to prepare them to meet their professional responsibilities. The purpose of this study was to examine health promotion students' advocacy/public policy involvement, training, and perceptions. Electronic surveys were disseminated nationwide to college students in health education and closely related programs. Of 477 student respondents, the most frequently indicated advocacy/public policy activity engaged in was voting (56%). The greatest benefit to advocacy was indicated as creating public awareness, while the most prevalent barrier reported was lack of familiarity with the legislation process. Less than one third of students reported receiving any training; however, training and the number of training sources were associated with greater involvement (p < .05). Comparisons by academic classification indicated that graduate students participated in more advocacy activities and reported significantly more benefits, barriers, knowledge, and self-efficacy compared with undergraduates. Regression analysis indicated that knowledge, self-efficacy, perceived benefits, and total number of training sources were significant predictors of advocacy involvement in both graduate and undergraduate student models, with age also contributing significantly to the graduate student model. Findings emphasize the need for increased training at earlier education levels to increase knowledge, self-efficacy, and advocacy/public policy involvement.